Energy-aware wireless systems with adaptive power-fidelity tradeoffs. - Raghunathan, V. (IEEE Transactions on VLSI systems)
Wireless networked embedded systems, such as multimedia terminals, sensor nodes, etc., present a rich domain for making energy/performance/quality tradeoffs based on application needs, network conditions, etc. Energy awareness in these systems is the ability to perform tradeoffs between available battery energy and application quality requirements. In this paper, we show how operating system directed dynamic voltage scaling and dynamic power management can provide for such a capability. We propose a real-time scheduling algorithm that uses runtime feedback about application behavior to provide adaptive power-fidelity tradeoffs. We demonstrate our approach in the context of a static priority-based preemptive task scheduler. Simulation results show that the proposed algorithm results in significant energy savings compared to state-of-the-art dynamic voltage scaling schemes with minimal loss in system fidelity. We have implemented our scheduling algorithm into the eCos real-time operating system running on an Intel XScale-based variable voltage platform. Experimental results obtained using this platform confirm the effectiveness of our technique